Advanced Smart Battery Management System with Adaptive Charging and Real-Time Fault Diagnostics for Electric Vehicles (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The rapid growth of electric vehicles (EVs) has increased so the need for efficient and reliable Battery Management Systems (BMS) to ensure safe and optimal battery operation. This paper presents the design and implementation of a smart BMS for a load-carrying electric vehicle powered by a 60 V, 60 Ah Lithium Iron Phosphate (LiFePO₄) battery. The system utilizes a 32-bit microcontroller integrated with a smart BMS to monitor key battery parameters such as voltage, current, and temperature. The proposed system incorporates features such as fault detection and alert mechanisms, adaptive on-board charging, and an LCD-based display for real-time monitoring. In addition, a multi-mode access system using NFC/Wi-Fi card, remote control, and key-based operation is implemented along with an anti-theft alarm to enhance vehicle security. The EV also includes a three-level gear system and reverse operation for improved usability. The system ensures reliable performance, enhanced safety, and efficient energy utilization. The proposed smart BMS provides a practical and effective solution for modern load-carrying electric vehicle applications.